Influência do componente florestal no desempenho agronômico da cultura da soja em sistema de integração Lavoura-Pecuária-Floresta - Tomazella, Arthur [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
The Crop-Livestock-Forest Integration System (ICLF), represents the interaction of agricultural, livestock and forestry activities. The Crop-Livestock (ICL) represents the interaction of agricultural, livestock activities. This kind of interaction between these activities leads to synergistic, null, or antagonistic effects, related to the factors of production. Therefore, we worked monitoring the productivity of the agricultural component (soybean), integrated in a ICL system and two ICLF systems which the difference between these ICLF system was only by the species of the forest component . The study was conducted in the city of Jaboticabal, SP, from June 2018 to March 2019.In relation to the forestry component, used in the treatment area, planting lines, rows, were positioned in the North-South direction, with 2 meters from the first planting line to the first forest component row. About the agricultural component, a soybean cultivar was used, with 45 centimeters spacing between rows. The results shows that there is a difference about the soybean productivity, between both systems, ICL and ICLF.

– O Sistema de Integração Lavoura-Pecuária-Floresta (ILPF), representa a interação de atividades agrícolas, pecuárias e florestais. Já o Sistema de Integração Lavoura-Pecuária (ILP) representa a interação de atividades agrícolas e pecuárias. Tal interação entre estas atividades, conduz à efeitos sinérgicos, nulos, ou antagônicos, relacionados aos fatores de produção. Em vista disso, foi realizado um trabalho, objetivando analisar a produtividade do componente agrícola (soja), integrado a um sistema ILP e dois sistemas ILPF, estes últimos que diferiam apenas na espécie do componente florestal. O estudo foi realizado na cidade de Jaboticabal, SP, no período de junho de 2018 a março de 2019. Em relação ao componente florestal, utilizado na área experimental, foram posicionadas linhas duplas de plantio em renques, na direção Norte-Sul, com de 2 metros entre linhas e de 20 metros entre renques. Em relação ao componente agrícola foi usada uma cultivar de soja, com espaçamento de 45 cm entre linhas. Os resultados demonstram que a implantação do sistema ILPF difere do sistema ILP, em relação a produtividade da soja.
Influence of the forest component on the agronomic performance of soybean in an integrated crop-livestock-forest integration system
Keywords: Soja; agricultura sustentável; pecuária; produtividade agrícola; eucalipto